Demografia i historia - Henry, Louis (Wydział Prawa i Administracji UAM, 1981)
The author reflects on relations between demography and history. He evaluates the role of demographic research in cognition of the past, and moves a problem to which extent demography is related to natural sciences. He arrives at the conclusion that historical demography embraces only a part of demography of the past, since it is restricted — on the one hand — by paleodemography in respect of the kind of research tools and statistical sources used and on the other — by contemporary demography. In the days to come historical demography should become an auxiliary science for history similarly as it is in case of archeology. The research results of historical demography can be, however, of direct importance not only for history but also for other sciences.
Demography and History